Depression and anxiety symptoms in Russian-speaking skilled immigrants living in Australia: A comparison with Anglo-Australians and Russian-speaking non-immigrants. (September 2021) - Demutska, Alla; Kiropoulos, Litza
Abstract: Data and systematic research on Australia's diverse immigrant population have been sparse. This study is the first empirical analysis of anxiety and depression symptoms in Russian-speaking skilled immigrants living in Australia. We compared levels of depression and anxiety symptoms in Russian-speaking skilled immigrants to Australia, Russian-speaking non-immigrants residing in one of the countries of the Former Soviet Union (FSU) and Anglo-Australians. 65 Russian-speaking immigrants from the FSU, 65 Russian-speaking non-immigrants residing in Russia, Ukraine, or Belarus, and 63 Anglo-Australians were recruited through social clubs, community web forums, churches, schools and universities. Participants completed online versions of the Centre for Epidemiologic Studies Depression Scale, the State-Trait Anxiety Inventory, the Interpersonal Support Evaluation List, the Perceived Stress Scale and socio-demographic questionnaires. Results indicated that levels of anxiety and depression were higher in Anglo-Australians compared to the Russian-speaking immigrant and the Russian-speaking non-immigrant groups after controlling for age, gender, relationship status, highest educational level, employment and health status. The outcomes of this study provide valuable insight into the mental health status of this under investigated group and can serve as the first step towards culturally informed mental health service delivery. Future research should address the limitations of the current study such as employing better sampling methods and using more culturally relevant scales to measure depression and anxiety.